Application of the Snowball Sample in the diagnostic based on factors that affect the productivity of Cherimoya production in MSEs: A case of study of Callahuanca and San Mateo de Otao, Peru - Sotelo, Fernando; Molina, Andrea; Rojas, Katty (Advances in Social Sciences Research Journal, 2018)
It is evident that economic poverty is one of the problems presented by underdeveloped countries, and that their reduction is related to the increase in productivity in MSEs, given the high impact they have represented over time. Many entities have identified the importance of agriculture in the economic sector of the country. Therefore, a diagnosis is necessary in the area. The purpose of this diagnosis is to have a reference of the environment from the general point of view, in which all the interactions, descriptions, particularities and existing processes can be observed. In this first stage of the diagnosis, it is carried out using a non-probabilistic sampling, which is a common method in the investigation. One of the many methods used for identifying diagnosis is the snowball sampling that allows finding the diagnosis of hidden populations where there is no way to know all the characteristics of a population. The benefit of using this type of sampling is that a single initial informant can put the researcher in contact with other sources. Further, based on the results obtained, it was identified that the causes of the problem of the Cherimoya sector were associated to 3 critical processes that reflected the non-productivity of this sector: process of planning management and production control, process of logistic management and process of quality management.